Pendidikan agama inklusif sebagai fondasi moderasi beragama: Strategi merawat keberagaman di Indonesia - Rumahuru, Yance Z.; Talupun, Johanna S. (KURIOS (Jurnal Teologi dan Pendidikan Agama Kristen), 2021)
The phenomenon of radicalism and religious extremism has strengthened in Indonesia in the last decade, even though Indonesia is known as a friendly and tolerant country. In fact, the religious education provided from elementary school to university has apparently not been able to build an inclusive religious perspective and attitude. It is assumed that religious education, including Christian Religious Education, which is taught is still oriented towards teaching a narrow doctrine so that many do not see diversity as an important context in the religious learning process. This article aims to promote inclusive religious education as the foundation of religious moderation in Indonesia. This study uses a qualitative approach, with the method of analyzing the results of previous studies related to the policy and implementation of religious education in Indonesia, as well as conducting observations and interviews regarding the practice of religious education in schools on a macro basis, and making comparisons with the results of available research. This study finds that a paradigm shift in religious education is needed, both at the level of policymakers and education implementers. This study offers an inclusive religious education paradigm, which is seen as being able to change the perspective and attitude of exclusive religion because it prioritizes mutual trust and respect for human equality. AbstrakFenomena radikalisme dan ekstrimisme agama semakin menguat di Indonesia pada dekade terakhir ini, padahal Indonesia dikenal sebagai negara yang ramah dan toleran. Bahkan, pendidikan agama yang diberikan sejak masa Sekolah Dasar hingga perguruan tinggi rupanya belum mampu membangun perspektif dan sikap beragama yang inklusif. Diasumsiskan bahwa pendidikan agama, termasuk Pendidikan Agama Kristen, yang diajarkan masih berorientasi pada pengajaran doktrin yang sempit, sehingga belum banyak melihat keberagaman sebagai salah satu konteks penting dalam proses pembelajaran agama. Artikel ini bertujuan mempromosikan pendidikan agama inklusif sebagai fondasi moderasi beragama di Indonesia. Kajian ini menggunakan pendekatan kualitatif, dengan metode analisis terhadap hasil kajian sebelumnya terkait kebijakan dan implementasi pendidikan agama di Indonesia, serta mengadakan pengamatan dan wawancara sehubungan dengan praktik pendidikan agama di sekolah secara makro, dan melakukan perbandingan dengan hasil-hasil penelitian yang tersedia.  Studi ini menemukan bahwa diperlukan perubahan paradigma pendidikan agama, baik pada level pengambil kebijakan maupun pelaksana pendidikan. Kajian ini menawarkan paradigma pendidikan agama inklusif, yang dipandang dapat mengubah perspektif dan sikap beragama eksklusif, karena mengutamakan sikap saling percaya dan penghargaan terhadap kesederajatan umat manusia.